(untitled) (International Journal of Ayurveda and Pharma Research, 2016)
It has been estimated that about 6 lacks infant and young children die from RSV annually, and if bacterial co infections are included this number may approach 10 lacks deaths annually. More than 2 million deaths are estimated to result each year the world over as a consequence of diarrheal disease in children of under five years. This statistic shows that children are more vulnerable to infection because their immune system is less or under developed. Ayurveda is a vast storehouse of knowledge relevant to human health, disease, medicines and general health-care. However mutual incomprehensibility of the terms and concepts has been a major impediment in meaningful dialogue between modern scientific medicine and Ayurveda. Some recent concepts of molecular medicine, immunology etc. have been found to have striking similarities with certain concepts of Ayurveda. Therefore, it is being realized that it might be possible to develop a relationship between modern medicine and Ayurveda. Here a comprehensive review of the Ayurvedic classical texts is presented to understand the concept of the Vyadhikshamatva w.s.r. to immunity.